Regulation of synthetic biology : bioBricks, biopunks and bioentrepreneurs - McLennan, Alison (Elgar studies in law and regulation, 2018)
This book explores the interplay between regulation and emerging technologies in the context of synthetic biology, a developing field that promises great benefits, and has already yielded fuels and medicines made with designer micro-organisms. For all its promise, however, it also poses various risks. Investigating the distinctiveness of synthetic biology and the regulatory issues that arise, Alison McLennan questions whether synthetic biology can be regulated within existing structures or whether new mechanisms are needed. Adopting an interdisciplinary approach, McLennan draws on diverse areas of law, the science of synthetic biology and the history and sociology of science. She concludes that synthetic biology presents novel regulatory challenges relating to environmental risk, biosafety, biosecurity and intellectual property.-